How Does Corporate Investment Respond to Increased Entry Threat? - Frésard, Laurent; Valta, Philip (The Review of Corporate Finance Studies, 2015)
We study how product-market interactions affect investment. We use reductions of import tariffs to examine how incumbents modify investment when the threat of rivals’ entry intensifies. Incumbents reduce investment by 7.2% in response to higher entry threat. Consistent with a strategic behavior, the investment reduction varies across market structures: it concentrates in markets in which competitive actions are strategic substitutes, where deterring entry is costly and investment makes incumbents look soft. Our results provide novel evidence on how and why firms’ interactions influence corporate investment. Received August 10, 2015; accepted December 1, 2015 by Editor Efraim Benmelech.